Handbook of nutrition and food (Taylor & Francis, 2014)
"Beginning with an overview of food and food constituents, the book outlines current nutrient analysis systems, techniques for data analysis, and food labeling. The book reviews nutrition science including terminology, biochemistry, nutrient-nutrient interactions, and comparative nutrition. There is a detailed assessment in section three on nutritional needs throughout the lifecycle. It highlights exercise and the value of vegetarian diets in health promotion and disease prevention. Section four considers issues surrounding nutritional assessment, screening, and monitoring tools including questionnaires, and anthropometric-, psychological-, and energy-assessments."--Provided by publisher.
Keywords: Food.; Diet therapy.; Diet.; elektronické knihy; electronic books